The Role of Management Accounting in Determining Dui'menre'in Bugis Traditional Wedding Traditions - Nur'Illiyyien; Neks Triani; Syarifuddin; Darwis Said (LP2M IAIN Palopo, 2025)
This research examines the shift in meaning of dui' menre' in Bugis society from a traditional symbol to a socio-economic burden. This tradition has serious consequences, including delayed marriage and elopement (silariang; Bugis), due to its often irrational nominal value and the pressure to maintain prestige. Through a qualitative approach, this study finds tension between the traditional meaning of dui' menre' as a marker of self-esteem (siri') and the financial reality of the younger generation, exacerbated by the gap with the principle of simplicity in Islam. As a solution, this study offers an alternative perspective by rationalizing its determination through a management accounting framework. Dui' menre' is analyzed as a project cost (wedding party) that requires strategic planning. The proposed framework combines target costing to set minimum costs based on real budgets, value-based pricing to calculate honor premiums fairly, and cost control mechanisms to ensure accountability. Thus, this study not only contributes academically by expanding the application of management accounting to the cultural realm, but also provides a practical framework for communities and traditional leaders to balance the preservation of traditions with financial sustainability and the alignment of Islamic values.